Tackling health inequalities in access to Child and Adolescent Mental Health Services (CAMHS) using neighbourhood profiling of administrative data - Harris, Rachel; Wilson, Scott (International Journal of Population Data Science, 2018)
Background Reducing health inequalities includes addressing access to and use of services, including considering how deprivation may affect service engagement and referrals. NHS Greater Glasgow and Clyde (NHSGGC) are close to the national average for most CAMHS benchmarking indicators, including waiting times, and referrals received and accepted. When comparing UK rates of Did Not Attends (DNA), however, NHSGGC were fourth highest in 2016. More detailed analysis of service use was thus of interest. While some service and patient risk factors are known, this study used data from NHSGGC’s electronic children’s health record system to develop neighbourhood profiles of access and use. Objectives To analyse activity within communities so health resources can be best targeted. To help clinical teams plan services and develop new models matched to local need. Methods Patient-level administrative data was linked to geographic and population data to identify outlying areas of demand. Data on referrals, open cases, appointments and DNAs were extracted and population-based analyses undertaken with 120,000 data points, linked to 273 neighbourhoods across NHSGGC. Findings Geomaps were used to highlight variation in activity, demand and population at neighbourhood and NHSGGC levels. Unexpectedly low levels of population reach (open cases/population under 18s) were found in some areas (Govanhill, 0.5%, relative to NHSGGC, 1.94%). Yet, the high level of DNAs in some East Glasgow areas is as one would predict given deprivation levels. Conclusions Findings have been used to identify potential improvements and to target communities who could benefit most. For example, West Dunbartonshire teams noticed high DNA rates in two neighbourhoods, both geographically distant from clinics. Satellite clinics have been introduced to improve attendance by reducing travel time and costs for families. Neighbourhood profiles have proved valuable in highlighting population based trends and supporting comparisons locally and relative to NHSGGC wide benchmarks.